2020
DOI: 10.1104/pp.20.00603
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Activation of Enoyl-CoA Reductase By An Acetyltransferase Complex Triggers Wheat Wax Biosynthesis

Abstract: The epidermal surface of bread wheat (Triticum aestivum) is coated with a hydrophobic cuticular wax layer that protects plant tissues against environmental stresses. However, the regulatory mechanism of cuticular wax biosynthesis remains to be uncovered in bread wheat. Here, we identified wheat Enoyl-CoA Reductase (TaECR) as a core component responsible for biosynthesis of wheat cuticular wax. Silencing of TaECR in bread wheat resulted in a reduced cuticular wax load and attenuated conidia germination of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 85 publications
1
40
0
Order By: Relevance
“…Powdery mildew caused by the fungal pathogen Blumeria graminis is a devastating disease in barley and wheat. Increasing evidence has revealed that B. graminis could utilize plant cuticular wax components to initiate their prepenetration processes such as conidial germination and appressorial development [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. Hansjakob et al reported that very-long-chain aldehydes could stimulate the in vitro conidial germination of B. graminis in a dose-dependent manner [ 86 , 87 ].…”
Section: Regulation Of Plant–fungal Pathogen Interaction By Cuticumentioning
confidence: 99%
See 1 more Smart Citation
“…Powdery mildew caused by the fungal pathogen Blumeria graminis is a devastating disease in barley and wheat. Increasing evidence has revealed that B. graminis could utilize plant cuticular wax components to initiate their prepenetration processes such as conidial germination and appressorial development [ 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. Hansjakob et al reported that very-long-chain aldehydes could stimulate the in vitro conidial germination of B. graminis in a dose-dependent manner [ 86 , 87 ].…”
Section: Regulation Of Plant–fungal Pathogen Interaction By Cuticumentioning
confidence: 99%
“…tritici ( Bgt ). Interestingly, the Bgt germination penalty on the TaKCS6- or TaECR -silenced wheat plants could be fully restored by the application of wild-type cuticular waxes or very-long-chain aldehydes, suggesting that the very-long-chain aldehydes were the wax signals provided by TaKCS6 and TaECR for stimulating Bgt conidia germination in bread wheat [ 91 , 92 ]. In Arabidopsis , Inada and Savory reported that the powdery mildew pathogen Golovinomyces orontii ( G. orontii ) could infect the mature rosette leaves of Arabidopsis , but its prepenetration processes such as conidial germination and appressorial formation were strongly inhibited on stems, fruits, and roots of Arabidopsis [ 93 ].…”
Section: Regulation Of Plant–fungal Pathogen Interaction By Cuticumentioning
confidence: 99%
“…In addition, regulation of crop-pathogen interactions by histone (de)acetylation was supported by studies on the crop HATs and HDACs (Ding et al, 2012;Liu et al, 2019;Jin et al, 2020;Kong et al, 2020a;Zhi et al, 2020). For instance, wheat HAT complex TaGCN5-TaADA2 activates wheat wax biosynthesis by mediating histone acetylation at the promoters of biosynthesis-related genes, thereby providing wax signals for the conidial germination of fungal pathogen Bgt (Table 1, Kong et al, 2020b). Rice HDAC OsHDT701 interacts with the rice RNase P subunit Rpp30 and negatively regulates rice defense responses to the fungal pathogen Magnaporthe oryzae (M. oryzae) and bacterial pathogen Xoo by mediating histone deacetylation at PRR and defense genes (Table 1, Ding et al, 2012;Li et al, 2021).…”
Section: Tachr729mentioning
confidence: 96%
“…Extensive work on B. graminis has shown that this pathogenic fungus exploits components of the plant epicuticular wax to induce pre-penetration processes. For instance, silencing 3-ketoacyl-CoA synthase 6 (KCS6) and enoyl-CoA reductase (ECR) in wheat (Triticum aestivum), both of which are important for VLCFA biosynthesis and the elongation reactions required for cuticular lipid biosynthesis, attenuates B. graminis spore germination (Wang et al, 2019;Kong et al, 2020). In line with these findings, Feng et al (2009) characterized Lip1, a lipase in B. graminis that is secreted onto the surface of fungal cell walls and possesses the ability to release alkanes and primary fatty alcohols from the epicuticular wax of wheat leaves.…”
Section: Epicuticular Waxes Are Major Determining Factors Of Plant-fungal Interactionsmentioning
confidence: 99%